Effect of new post emergence herbicides on weed dynamics in wet seeded rice - Prameela, P.; S Menon, Syama; V Menon, Meera (Journal of Tropical Agriculture, 2014)
An experiment was conducted in Kole lands of Thrissur, Kerala, India, during October 2011 to February 2012 to study the effect of various post emergent herbicides on weed flora and density in wet seeded rice. The herbicidal treatments included application of three graminicides (metamifop, fenoxaprop- p-ethyl and cyhalofop-butyl), graminicides with follow up spray of herbicides (Almix, carfentrazone and ethoxy sulfuron) to kill non grassy weeds and herbicides with broad spectrum activity (bispyribac sodium, penoxsulam and azimsulfuron). Hand weeded and unweeded controls were also included. The results showed that grasses were the dominant weed flora followed by broad leaved weeds and sedges. Echinochloa was the main grass weed whose density was 21 m-2 in unweeded control whereas the lowest density (3-5 m -2) was registered in graminicide applied plots. The highest broad leaved weed population was in metamifop sprayed plots. The lowest grass population was noticed in bispyribac sodium which was free of sedges also. At harvest stage of rice, in hand weeded plots the broad leaved weed Lindernia crustacea alone was present. The best herbicide treatment with low weed dry matter production was fenoxaprop- p- ethyl or cyhalofop-butyl with follow up spray of Almix. Bispyribac sodium registered the highest weed control efficiency next to hand weeding which was comparable to application of cyhalofop- utyl/fenoxaprop-p-ethyl/metamifop with follow up spray of Almix.